2021
DOI: 10.3390/diagnostics11122337
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation and Surgical Simulation for Osteochondritis Dissecans of the Elbow Using Three-Dimensional MRI-CT Image Fusion Images

Abstract: We used our novel three-dimensional magnetic resonance imaging-computed tomography fusion images (3D MRI-CT fusion images; MCFIs) for detailed preoperative lesion evaluation and surgical simulation in osteochondritis dissecans (OCD) of the elbow. Herein, we introduce our procedure and report the findings of the assessment of its utility. We enrolled 16 men (mean age: 14.0 years) and performed preoperative MRI using 7 kg axial traction with a 3-Tesla imager and CT. Three-dimensional-MRI models of the humerus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, the combination of different imaging modalities may contribute to further developments in the field of metal artifact reductions. In intraarticular lesion imaging, a novel technique for the three-dimensional fusion of MRI and CT has been introduced [ 89 , 90 ]. Each imaging technique may compensate for the other’s shortcomings and contribute to an accurate diagnosis by clinicians.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…In addition, the combination of different imaging modalities may contribute to further developments in the field of metal artifact reductions. In intraarticular lesion imaging, a novel technique for the three-dimensional fusion of MRI and CT has been introduced [ 89 , 90 ]. Each imaging technique may compensate for the other’s shortcomings and contribute to an accurate diagnosis by clinicians.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…The image fusion technique could possibly combine the merits of CT and MRI and get a better model of the tumor in assisting clinical decisions 18,19 . Pilot attempts have been utilized in other organs using CT and MRI fusion techniques in guiding clinical practice 20–22 . We previously reported a successful case using the CT/MRI fusion 3D model to evaluate and plan the surgery of a pelvic osteosarcoma patient 23 .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Pilot attempts have been utilized in other organs using CT and MRI fusion techniques in guiding clinical practice. [20][21][22] We previously reported a successful case using the CT/MRI fusion 3D model to evaluate and plan the surgery of a pelvic osteosarcoma patient. 23 No study has been reported to compare the accuracy of the CT/MRI fusion model with CT only model.…”
mentioning
confidence: 99%
“…If 3D-image-based virtual reduction can aid in the restoration of the pre-injury anatomy of fractured bones, it will be able to provide a model for 3D-printed implant fabrication and can be used as a highly reliable pre-surgical simulation and fracture management tool. A more accurate surgical approach can be realized with greatly reduced operation times, minimizing the associated surgical complications [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. However, to be helpful to the clinical field, the verification of the accuracy of 3D-image-based virtual reduction should be determined.…”
Section: Introductionmentioning
confidence: 99%